Effect of Treatment with Colchicine after Acute Coronary Syndrome on Major Cardiovascular Events: A Systematic Review and Meta-Analysis of Clinical Trials. (13th April 2022) - Razavi, Erfan; Ramezani, Akam; Kazemi, Asma; Attar, Armin
Abstract : Aim . Colchicine as an anti-inflammatory drug might be effective in the treatment of atherosclerosis, an inflammatory-based condition. The aim of this systematic review and meta-analysis was to evaluate the impact of colchicine on acute coronary syndrome (ACS). Methods . We searched SCOPUS, PubMed, and Web of Science up to September 27, 2020. All clinical trials which evaluated the effect of colchicine on ACS patients and reported high-sensitivity C-reactive protein (hs-CRP) serum level or gastrointestinal (GI) adverse events with at least 5-day follow-up or death, myocardial infarction (MI), and stroke with at least 30-day follow-up as outcomes were included. Results . Finally, seven publications were analyzed. The results of our study revealed that colchicine has a marginally significant effect on hs-CRP attenuation. Furthermore, colchicine manifested promising results by declining the risk of stroke by 70%. However, MI and primary composite endpoint did not differ between the colchicine and noncolchicine groups. Although colchicine did not significantly increase GI adverse events in the pooled analysis, the dose-dependent effect was detected. Low-dose consumption can avoid GI side effects of colchicine. Conclusion . Colchicine has shown some molecular and clinical promising results in ACS patients. The lack of effect of colchicine on MI and all-cause mortality can be partly attributed to the limitations of previous studies. Since colchicine is an inexpensive and easy-to-access drug that has shown to be safe in low-dose regimens in the clinical setting; it would be worthy that future large-scale well-designed clinical trials address this issue by resolving the limitations of previous investigations.